2013
DOI: 10.4172/2167-0501.s1-006
|View full text |Cite
|
Sign up to set email alerts
|

Connexin-36 Knock-Out Mice have Increased Threshold for Kindled Seizures: Role of GABA Inhibition

Abstract: Blockade of gap junctions (GJs) has been shown to reduce seizures in different epilepsy models. Gap junctionmediated, electrically-coupled neuronal networks have been implicated in neuronal synchronization, which is the hallmark of seizure activity. To further understand the role of GJs in seizures, in particular hippocampal seizures, we evaluated electrophysiological responses in the dentate gyrus subfield of the hippocampus, including GABA-mediated recurrent inhibition, seizuregenic stimulation, and seizure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Among them, MFQ, an FDA-approved antimalarial compound, is used for the prevention or treatment of mild and moderate malaria 20 , with neuropsychiatric side effects 14,18,21 . Later, it was discovered that MFQ specifically blocks Cx36 GJC, contributing to these side effects, such as spreading depression, NMDAR-mediated neuronal death, tremor, motor deficits, convulsant, stage IV seizures, cell death upon oxygenglucose deprivation, and hypersensitivity to pain [22][23][24][25][26][27][28][29] . Additionally, it is noteworthy that MFQ exhibits 10-to 100-fold higher sensitivity to Cx36 (IC50 value of 310 nM) and Cx50 (IC50 value of 1.1 μM) compared to other connexins.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, MFQ, an FDA-approved antimalarial compound, is used for the prevention or treatment of mild and moderate malaria 20 , with neuropsychiatric side effects 14,18,21 . Later, it was discovered that MFQ specifically blocks Cx36 GJC, contributing to these side effects, such as spreading depression, NMDAR-mediated neuronal death, tremor, motor deficits, convulsant, stage IV seizures, cell death upon oxygenglucose deprivation, and hypersensitivity to pain [22][23][24][25][26][27][28][29] . Additionally, it is noteworthy that MFQ exhibits 10-to 100-fold higher sensitivity to Cx36 (IC50 value of 310 nM) and Cx50 (IC50 value of 1.1 μM) compared to other connexins.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has examined the roles of Cx36 in the pathogenesis of seizures, but there has been no consensus on whether Cx36 increases or decreases seizure susceptibility (Gajda et al, 2005 ; Jacobson et al, 2010 ; Voss et al, 2010 ; Shin, 2013 ). Jacobson et al ( 2010 ) found that Cx36 knockout mice exhibited an increase in seizure-like behaviors following the administration pentylenetetrazol (PTZ; a GABA(A)-receptor antagonist), indicating that normal expression of Cx36 may be protective against seizure-inducing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has examined the roles of Cx36 in the pathogenesis of seizures, but there has been no consensus on whether Cx36 increases or decreases seizure susceptibility (Gajda, Szupera, Blazsó, & Szente, 2005;Jacobson et al, 2010;Shin, 2013;Voss, Mutsaerts, & Sleigh, 2010a). Jacobson et al (2010) found that Cx36 knockout mice exhibited an increase in seizurelike behaviors following the administration pentylenetetrazol (PTZ; a GABA(A)-receptor antagonist), indicating that normal expression of Cx36 may be protective against seizure-inducing conditions.…”
Section: Introductionmentioning
confidence: 99%